Caffeine Compromises Proliferation of Human Hippocampal Progenitor Cells - Houghton, Vikki; Du Preez, Andrea; Lefèvre-Arbogast, Sophie; de Lucia, Chiara; Low, Dorrain Y.; Urpi-Sarda, Mireia; Ruigrok, Silvie R.; Altendorfer, Barbara; González-Domínguez, Raúl; Andres-Lacueva, Cristina; Aigner, Ludwig; Lucassen, Paul J.; et al. (Frontiers in Cell and Developmental Biology, 2020)
The age-associated reduction in the proliferation of neural stem cells has been associated with cognitive decline. Numerous factors have been shown to modulate this process, including dietary components. Frequent consumption of caffeine has been correlated with an increased risk of cognitive decline, but further evidence of a negative effect on hippocampal progenitor proliferation is limited to animal models. Here, we used a human hippocampal progenitor cell line to investigate the effects of caffeine on hippocampal progenitor integrity and proliferation specifically. The effects of five caffeine concentrations (0mM=control, 0.1mM~150mg, 0.25mM~400mg, 0.5mM~750mg, and 1.0mM~1500mg) were measured following acute (1 day) and repeated (3 days) exposure. Immunocytochemistry was used to quantify hippocampal progenitor integrity (i.e., SOX2- and Nestin-positive cells), proliferation (i.e., Ki67-positive cells), cell count (i.e., DAPI-positive cells), and apoptosis (i.e., CC3-positive cells). We found that progenitor integrity was significantly reduced in supraphysiological caffeine conditions (i.e., 1.0mM~1500mg), but relative to the lowest caffeine condition (i.e., 0.1mM~150mg) only. Moreover, repeated exposure to supraphysiological caffeine concentrations (i.e., 1.0mM~1500mg) was found to affect proliferation, significantly reducing %Ki67-positive cells relative to control and lower caffeine dose conditions (i.e., 0.1mM~150mg and 0.25mM~400mg). Caffeine treatment did not influence apoptosis and there were no significant differences in any measure between lower doses of caffeine (i.e., 0.1mM, 0.25mM, 0.5mM) - representative of daily human caffeine intake - and control conditions. Our study demonstrates that dietary components such as caffeine can influence neural stem cell integrity and proliferation and may be indicative of a mechanism by which diet affects cognitive outcomes.